UTERINE RUPTURE DURING PREGNANCY: A COMPREHENSIVE SYSTEMATIC REVIEW - Christian, Roy; Pieter Hetharia, Frenki; Bangkit Sumardi, Franky; Dwi Rahayu, Inggit (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Uterine rupture, a rare but serious obstetric condition involving a tear through the uterine wall, has varying incidences globally, with scarred uteri, morbidly attached placenta, grand multiparity, and oxytocin use being common risk factors. This systematic review aims to comprehensively analyze the literature on uterine rupture during pregnancy, focusing on risk factors, geographical incidence variations, etiological patterns, impact of medical interventions, and maternal outcomes, with a goal to enhance understanding, identify preventive strategies, and improve clinical management. Method: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 11 results. After looking at the titles and summaries, we found 9 papers that fit our criteria. At first, we excluded several articles because they were written in review style and case reports. But after reading the full papers carefully, we included five papers in our final analysis. These papers included a retrospective observational study, prospective study, and retrospective study. Conclusion: In conclusion, uterine rupture (UR) is a catastrophic event requiring heightened vigilance in pregnant women with high-risk factors to mitigate severe consequences for both obstetricians and patients. Trials of labor after cesarean (TOLAC), a safe delivery option, faces challenges in Shanghai and China, and the risk of uterine rupture emphasizes the need for evaluating dosages and duration of prostaglandins and oxytocin. Our series highlights the grave neonatal prognosis of uterine rupture, stressing the importance of timely management and recognizing fetal heart rate abnormalities. The URIDA investigation, the largest database on UR during pregnancy, reveals insights into the association between previous uterine surgery, leiomyoma, and UR, emphasizing the need for early diagnosis and immediate treatment to minimize complications and ensure favorable outcomes in both the index and subsequent pregnancies.